Wedded to Warfare: Forced Marriage in Rebel Groups - Donnelly, Phoebe Grace. (Tufts University. Tisch Library., 2019)
Why do rebel groups create systems of forced marriage? In this dissertation, I build a theory of forced marriage based on original fieldwork examining two rebel groups in East Africa, Al-Shabaab (in Somalia and Kenya) and the Lord's Resistance Army or LRA (in northern Uganda). I also ask, what explains the different forms of forced marriage by rebel groups? And finally, what is the relationship between forced marriage and other gendered decisions by rebel groups? All rebel groups care about cohesion, yet rebel groups that use forced marriage have specific challenges related to cohesion. Rebel groups that are composed of abducted members need to build internal cohesion and have a centralized system of forced marriage as seen in the case of the LRA. Another model of forced marriage is for groups that govern a region and need to create external cohesion - a term I created to describe efforts by rebel groups to build connections to a large civilian population. If a rebel group is seeking to build external cohesion, they will have a decentralized system of forced marriage as illustrated by the case of Al-Shabaab. Rebel groups that use forced marriage not only have a strategic need related to cohesion, but also have a unique ideology which I describe as an ideology of social control. Rebel groups with ideologies of social control want to create a new ideal community and this community has specific standards of behavior for men, women, boys, and girls. For rebel groups with an ideology of social control, their power comes not from controlling territory, but instead from controlling men, women, boys, and girls. Finally, I examine the influence of forced marriage on decisions related to the gendered division of labor and the use of sexual violence outside of forced marriages. This study demonstrates that understanding forced marriage reveals essential information about rebel group behavior related to strategy, ideology, tactics, and organization.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Dyan Mazurana.; Committee: Richard Shultz, and Dara Cohen.; Keyword: International relations.